RESTful API with Express - Dennison, Justin; Bryan, Wes; Memos, Zachary (Packt Publishing, 2024)
Embark on a detailed journey into creating RESTful APIs with the Express framework. This course starts with setting up a Node-based project and installing Express. You'll learn essential concepts like routing, middleware, and data modeling, crucial for robust API development. The course covers CRUD operations within RESTful APIs, ensuring a solid grasp of backend fundamentals. Progressing further, you'll build a simple Express application, with detailed explanations of request and response objects, middleware creation, and integrating third-party middleware. Hands-on learning with real-world examples guides you through building routes and managing data. Tools like Postman are introduced for testing and refining your API. In advanced topics, you'll focus on data persistence and adding complex features like location tracking. Discussions on universally unique identifiers (UUIDs) will enhance your technical skills. By course end, you'll have a comprehensive understanding of building scalable and efficient RESTful APIs with Express, ready to apply your skills in real-world projects.